2016
DOI: 10.1016/j.jviromet.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of avian influenza virus H5N1 in chicken tracheal samples using an impedance aptasensor with gold nanoparticles for signal amplification

Abstract: Highly pathogenic avian influenza virus H5N1 is a continuous threat to public health and poultry industry. The recurrence of the H5N1 led us to develop a robust, specific, and rapid detection method for the virus. In this study, an impedance aptasensor was developed for the virus detection using specific H5N1 aptamer and a gold interdigitated microelectrode. Streptavidin was immobilized on the microelectrode surface and biotin labeled H5N1 aptamer was bound to the immobilized streptavidin. The microelectrode w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 38 publications
(44 reference statements)
0
38
0
1
Order By: Relevance
“…In the Li’s lab, a highly specific DNA aptamer that can bind H5N1 virus with high affinity was selected. Using this aptamer, other authors have developed different aptasensors based on Surface Plasmon Resonance (SPR) [148], a quartz crystal microbalance (QCM) aptasensor crosslinked polymer hydrogel [149] and several aptasensors based on impedance methods [150,151,152]. These aptasensors were able to detect H5N1 quickly and/or with more sensitivity than antibody-based biosensors.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Li’s lab, a highly specific DNA aptamer that can bind H5N1 virus with high affinity was selected. Using this aptamer, other authors have developed different aptasensors based on Surface Plasmon Resonance (SPR) [148], a quartz crystal microbalance (QCM) aptasensor crosslinked polymer hydrogel [149] and several aptasensors based on impedance methods [150,151,152]. These aptasensors were able to detect H5N1 quickly and/or with more sensitivity than antibody-based biosensors.…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…The impedance aptasensor with microfluidics chips has a lower detection limit than the SPR-based aptasensor [148] and the same sensitivity as the QCM aptasensor [149], but the QCM-based aptasensors are not practical for in-field use due to the QCM’s predisposition to environmental noise. The major advantage of the impedance aptasensor with gold nanoparticles for signal amplification described by Karash et al is that it requires a small sample volume and is cheaper than the detection platforms based on QCM or that use interdigitated electrode microfluidic chips [152]. Recently, Nguyen et al developed a sandwich-type SPR-based biosensor for the detection of H5Nx viruses using a pair of aptamers selected against a mixture of H5Nx whole viruses using Multi-GO SELEX [153].…”
Section: Aptamers For Virus Diagnosis and Treatmentmentioning
confidence: 99%
“…The avian influenza H5N1 virus was recently detected using electrochemical aptasensors . H5N1 is responsible for the death of approximately 400 million birds, but due to its mutation, it has also infected humans.…”
Section: Aptamer‐based Electrochemical Biosensorsmentioning
confidence: 99%
“…136 The anti-HA aptamer was later immobilized onto a gold interdigitated microelectrode for the development of a rapid H5N1 detection method, and the method had the detection limit of 1 hemagglutination unit (HAU) in the tracheal chicken swab samples spiked with the H5N1 virus. 141 Other aptamers for influenza virus detection target whole virus particles. [142][143][144] Lai et al carried out screening and found an influenza A virus-specific aptamer, 142 which was later incorporated into an integrated microfluidic chip for H1N1 detection, and the limit of detection was found to be 0.032 HAU.…”
Section: Influenza Virusmentioning
confidence: 99%